2010
DOI: 10.1021/es9029649
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Distributions of Plutonium and 137Cs in Lacustrine Sediments in Northwestern China: Quantifying Sediment Accumulation Rates and Source Identifications

Abstract: We investigated the vertical distributions of 239+240Pu and 137Cs activities and 240Pu/239Pu atom ratios in two lakes in northwestern China. The 240Pu/239Pu atom ratio from the Chinese nuclear test (CNT) site at Lop Nor is too complicated to identify the regional fallout source. However, radionuclides from the test site may be resolved mainly by the vertical distribution of radionuclides because there is no overlap between the global fallout peak and the local fallout peak. We analyzed Pu isotopes and 137Cs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 30 publications
9
55
0
Order By: Relevance
“…Two extremely low 240 Pu/ 239 Pu atom ratios of 0.059 and 0.085 were observed for YM1 (20–25 cm) and YM2 (6–8 cm) locations, respectively. Similar results were also reported in lake sediments collected in northwest China and the CNTs were suggested to contribute to the Pu contamination in these lakes 18 19 . The present results for the soil core samples collected downwind from the CNT site further revealed that the 240 Pu/ 239 Pu atom ratios derived from the regional fallout of the CNTs could be lower than the global fallout value.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Two extremely low 240 Pu/ 239 Pu atom ratios of 0.059 and 0.085 were observed for YM1 (20–25 cm) and YM2 (6–8 cm) locations, respectively. Similar results were also reported in lake sediments collected in northwest China and the CNTs were suggested to contribute to the Pu contamination in these lakes 18 19 . The present results for the soil core samples collected downwind from the CNT site further revealed that the 240 Pu/ 239 Pu atom ratios derived from the regional fallout of the CNTs could be lower than the global fallout value.…”
Section: Resultssupporting
confidence: 87%
“…For example, Jin et al 16 reported a 240 Pu/ 239 Pu atom ratio of 0.16 in the soil of Gansu Province. More recently, Wu et al 18 and Liao et al 19 found 240 Pu/ 239 Pu atom ratios of 0.103 and 0.080 in deep sediments collected from Lake Sugan in the downwind direction from the CNT site and from Lake Boston in the upwind direction, respectively. These results suggested that the 240 Pu/ 239 Pu atom ratio from the CNTs could also be lower than the global fallout value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar 240 Pu/ 239 Pu atomic ratios of 0.157 ~ 193 with an average of 0.182 ± 0.012 (1σ) have also been reported in a sediment core collected in Lake Sihailongwan, northeast China (42°20′N, 126°50′E)33. In addition, the measured 239 + 240 Pu/ 137 Cs activity ratios (Supplementary Table S1 online) in all surface soil samples (~0.045, decay corrected to 1 st Sept. 2009) agreed well with the reported values (0.030 ~ 0.043) in soils contaminated only by global atmospheric fallout34.…”
Section: Discussionsupporting
confidence: 80%
“…Based on these facts, it might be concluded that the direct contribution of the close-in fallout from Chernobyl accident to the Pu in soils in the northeast China should be negligible. Moreover, the reported 240 Pu/ 239 Pu atomic ratios of close-in fallout Pu in the Semipalatinsk NWT (0.04 ~ 0.07)14 (more than 3400 km distance to the present sampling locations), the Chinese NWT (0.08 ~ 0.103)3338 and from the Kyshtym accident (0.0282 ± 0.0002)45 were all obviously lower than those (around 0.18) observed in this work, indicating that any close-in fallout contribution from these two NWT sites as well as from Kyshtym site could also be negligible in our sampling sites.…”
Section: Discussionmentioning
confidence: 57%